8t+3(3t-2)=-5t-10

Simple and best practice solution for 8t+3(3t-2)=-5t-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8t+3(3t-2)=-5t-10 equation:


Simplifying
8t + 3(3t + -2) = -5t + -10

Reorder the terms:
8t + 3(-2 + 3t) = -5t + -10
8t + (-2 * 3 + 3t * 3) = -5t + -10
8t + (-6 + 9t) = -5t + -10

Reorder the terms:
-6 + 8t + 9t = -5t + -10

Combine like terms: 8t + 9t = 17t
-6 + 17t = -5t + -10

Reorder the terms:
-6 + 17t = -10 + -5t

Solving
-6 + 17t = -10 + -5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '5t' to each side of the equation.
-6 + 17t + 5t = -10 + -5t + 5t

Combine like terms: 17t + 5t = 22t
-6 + 22t = -10 + -5t + 5t

Combine like terms: -5t + 5t = 0
-6 + 22t = -10 + 0
-6 + 22t = -10

Add '6' to each side of the equation.
-6 + 6 + 22t = -10 + 6

Combine like terms: -6 + 6 = 0
0 + 22t = -10 + 6
22t = -10 + 6

Combine like terms: -10 + 6 = -4
22t = -4

Divide each side by '22'.
t = -0.1818181818

Simplifying
t = -0.1818181818

See similar equations:

| 5-2x/7=9/14 | | 5(3x-6)-3(x+1)-19x= | | 1/8+y=-7/16 | | -96=z+-83 | | 3x-3=21x+9 | | 8x+7=87 | | 4(-4y^5)= | | 3x=2x+17 | | x-1/7=13/14 | | (6x+1)(x-7)=0 | | 3z-5-z+3=0 | | 5/8x+7=-3/8x | | 14x-13/8-13x=10/8+3/8 | | -0.8x+0.5x-6=9 | | 6n^2=-8n-1 | | x-1/3=2x/5+1/15 | | x+x+15=x+45+x+40+x+25 | | 7z+10-4z=8+2z+10 | | y-13/23=-5/23 | | 6-1/2x=3/5 | | 2x-(x+2)-(x-2)=x-10 | | 2(n-3)-(4-5n)=6n | | f+-63=27 | | 5x^3-3x^2=2 | | (8x+7)(x-4)=0 | | -16(y+1)+5(4y-4)=3(y-3)+10 | | 4q+2=3q-2 | | 57.99-0.11d=58.54 | | 28x-4+6-15x-12x-20=-6 | | 7b+2b=63 | | 2x+15=3x+110 | | 5(7+w)=4(6+w) |

Equations solver categories